Studi Keragaman dan Kekerabatan Padi Lokal Asal Kabupaten Siak Berdasarkan Karakter Kualitatif - Isnaini Isnaini; Fetmi Silvina; Nur Fadila Mora (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2023)
This study aims to determine the diversity accessions of Siak Regency’s local rice. The study was conducted for six months, from May to October 2018 at Experimental Garden of Agriculture Faculty, Riau University. This study used descriptive qualitative analysis method based on agronomic and morphological characters, as well as characterization activities on 21 local rice accessions. There are 10 morphological characters with low diversity, such as the surface, leaf surface, leaf tongue shape, leaf neck color, leaf ear color, leaf book color, leaf tongue color, grain tip color and the color of the pistil. There are five morphological characters with rather low diversity, such as the presence of lemmapalea hair, the color of stem segments, the color of leaf blades, panicle shaft and vigor. There are five morphological characters with quite high diversity, such as yellowing of leaves, panicle discharge, panicle type, secondary panicle branches and leaf midrib color also three morphological characters with high diversity, such as lemmapalea color, grain tip fur and grain tip fur color. While the agronomic character with a rather low diversity is vigor and there are three characters with quite high diversity, such as the stiffness of stem, yellowing of leaves and panicle discharge. Keywords: Agronomy, diversity, local rice, morphology.